ANALISIS YURIDIS TERHADAP WASIAT WAJIBAH DALAM PRESPEKTIF FIKIH ISLAM (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA TENTANG AHLI WARIS YANG BERAGAMA NON-MUSLIM) - VIKA SYAFITRI (PREMISE LAW JURNAL, 2015)
Giving a will is one of the methods in transfering property from someone to someone else. It is regulated in the Compilation of the Islamic Law as it stipulated in the Presidential Decree No. 1/1991, Chapter V, from Article 194 to Article 209 of the Compilation of the Islamic Law in the Book of Fiqh. Aticle 194 up to Article 208 regulate common will, while Article 209 regulates specific will for adopted child or adoptive parents. Based on several jurisprudences of the Supreme Court of the Republic of Indonesia, it is found that wajibah will is also given to non-Moslem heirs. It is found in the Ruling of the Supreme Court of the Republic of Indonesia No. 368.K/AG/1995, in the Ruling of the Supreme Court of the Republic of Indonesia No. 51.K/AG/1999, and in the Ruling of the Supreme Court of the Republic of Indonesia No. 16.K/AG/2010. These Rulings of the Supreme Court of the Repubic of Indonesia give wajibah will to non-Moslem heirs so that the jurisprudences are different from the concept of the Islamic Fiqh in which the heir of another religion is prohibited to inherit the property of the testator who is Moslem. Keywords: Wajibah Will, Islamic Fiqh, Heirs